PENYULUHAN DAN SOSIALISASI PROGRAM BPJS KESEHATAN BAGI MASYARAKAT DI KELURAHAN GADANG KOTA BANJARMASIN - Normajatun Normajatun; Umar Makawi; Abdul Haliq (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2016)
This study aimed to find out the description: 1) job satisfaction and employee performance, and 2) the influence of job satisfaction against the performance of employees. Research method using the method of survey sampling with saturated. Data were collected using a questionnaire and further analyzed by using simple regression techniques. Data processing using the help of the program SPSS (Statistical Product Service Solution) for Window 21.0. The research results of the descriptive analysis show, good job satisfaction or employee performance can be said to be very good although not optimal as expected institution. The results of the statistical analysis shows that job satisfaction, the effect on the performance of employees. This indicates the variable job satisfaction with five indicators is a unified, integrated and synergistic able to encourage performance improvement officer.Keywords:  Job satisfaction, performance of employees